Measuring Fish Sustainability, Efficiency, Justice, and Capability in Community-Based Economic Development - Amrizal Siagian; Zainal Arifin Hoesein (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
The development of Indonesia’s new capital city, Nusantara (IKN), is designed as a symbol of the nation’s economic and social transformation toward a sustainable, community-based city. However, the sustainability of this development cannot be assessed solely through economic growth, but also through the extent to which public policy ensures institutional efficiency, social justice, and human empowerment. This article proposes an integrative approach that combines Richard Posner’s theory of legal efficiency, John Rawls’s distributive justice, and Amartya Sen’s capability approach. Through conceptual analysis, the paper demonstrates that the sustainability of IKN depends on the synergy between efficient governance, equitable distribution of benefits, and the strengthening of citizens’ capabilities as agents of development. Efficiency without justice leads to social exclusion; justice without efficiency creates stagnation; and both, without capability, undermine the human meaning of development. Therefore, the integration of these three approaches is essential as an ethical and normative foundation to ensure that IKN becomes an inclusive, productive, and just city.